Human Resource Business Acumen and Social Capital Applications in the African Context - Schultz, Cecile M.; Nel, Pieter S. (Archives of Business Research, 2020)
A theoretical review of business acumen and social capital was conducted that would apply to human resource management practice to identify the desired behaviour of high-performing human resource professionals. The links of intellectual capital to human capital and organisation capital are necessary to contextualise social capital and its link with human capital resources and business acumen. A conceptual framework was proposed, consisting of business aspects, personal attributes and relationships to enhance human resource professionals’ business acumen. HR business acumen consists mainly of business aspects, personal attributes and relationships to enhance social capital. Specific business aspects involve thinking, knowledge, orientation and skills. An HR professional needs to possess executive-level thinking and systems thinking. They also must have business knowledge, a strategic orientation and skills such as financial literacy and being able to do metrics. Personal attributes such as agility, attitude, innovation, creativity, leadership, trustworthiness and responsiveness are of the essence. Lastly, relationships entail shared norms and values, trust, engagement and collaboration.